ANÁLISE TERMOGRÁFICA DA UTILIZAÇÃO DE COBERTURA VEGETADA EM GUARITAS DE FIBRA DE VIDRO - Krüger, Eduardo; Drach, Patricia; Tamura, Cintia; Kaviski, Francine (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In light-weight, security booths built in fiberglass, due to their poor thermal performance, the use of adequate roof materials can minimize heat gains in summer while avoiding heat losses in winter. Green roofs are among the building components that can contribute to indoor thermal stabilization while promoting temperature reductions in summer. The present study aimed to evaluate the use of a green roof in fiberglass security booths. Two modules were tested, one with and another without a green roof, under warm conditions in a subtropical location. The technique explored in this paper is based on thermography analysis. Results showed a higher thermal performance of the green roof in terms of mean temperature reduction at the ceiling when compared to the conventional roof in such structures.